Maternal influenza vaccination relates to receiving relevant information among pregnant women in Japan - Aiko Shono; Shu-Ling Hoshi; Masahide Kondo (Taylor & Francis Group, 2020)
Maternal vaccination for seasonal influenza is currently not listed as a routine vaccination in the national vaccination schedule of Japan. However, many pregnant women voluntarily receive an influenza vaccination. We explored the factors related to influenza vaccine uptake. We particularly focused on factors related to any recommendation, such as advice or suggestions from another individual. We conducted a cross-sectional web-based questionnaire survey in Japan among pregnant women or mothers who had recently given birth in March 2017 and 2018. Logistic regression models were used to determine the factors influencing vaccination uptake. Key individuals regarding maternal vaccination were examined using the network visualization software Gephi. The total number of valid responses was 2204 in 2017 and 3580 in 2018. Over 40% of respondents had been vaccinated with the seasonal influenza vaccine at some point in both years. Of the vaccinated respondents, over 80% received advice regarding the influenza vaccination. Obstetricians were the most common source of advice in both years. Among respondents who chose more than two sources, the largest link in the network of sources was found between the obstetrician and family members. Attention to public concern or potential recommenders, by public health authorities, not just pregnant women, about the benefits of maternal influenza vaccination is important.